Imposing economic constraints in nonparametric regression: survey, implementation and extension - Daniel J. Henderson; Christopher F. Parmeter (Institute for the Study of Labor (IZA), 2009)
Economic conditions such as convexity, homogeneity, homotheticity, and monotonicity are all important assumptions or consequences of assumptions of economic functionals to be estimated. Recent research has seen a renewed interest in imposing constraints in nonparametric regression. We survey the available methods in the literature, discuss the challenges that present themselves when empirically implementing these methods and extend an existing method to handle general nonlinear constraints. A heuristic discussion on the empirical implementation for methods that use sequential quadratic programming is provided for the reader and simulated and empirical evidence on the distinction between constrained and unconstrained nonparametric regression surfaces is covered.
urn:nbn:de:101:1-2009041483
Keywords: J20; J30; C14; 330; Constraint weighted bootstrapping; Hessian; concavity; identification; earnings function; Regression; Nichtparametrisches Verfahren; Nichtlineare Optimierung; Bildungsertrag; Monte-Carlo-Methode; Theorie